2014
DOI: 10.1111/jan.12509
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review evaluating the impact of online or blended learning vs. face‐to‐face learning of clinical skills in undergraduate nurse education

Abstract: The available evidence suggests that online learning for teaching clinical skills is no less effective than traditional means. Highlighted by this review is the lack of available evidence on the implementation of a blended learning approach to teaching clinical skills in undergraduate nurse education. Further research is required to assess the effectiveness of this teaching methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
330
1
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(425 citation statements)
references
References 33 publications
(128 reference statements)
24
330
1
24
Order By: Relevance
“…The findings from our review of student skills are in keeping with a systematic review evaluating the impact of online or blended and face-to-face learning of clinical skills in undergraduate nurse education (McCutcheon, Lohan, Traynor & Martin, 2015). On the basis of 19 published papers, the authors concluded that online teaching of clinical skills was no less effective than traditional means.…”
Section: Discussionmentioning
confidence: 67%
“…The findings from our review of student skills are in keeping with a systematic review evaluating the impact of online or blended and face-to-face learning of clinical skills in undergraduate nurse education (McCutcheon, Lohan, Traynor & Martin, 2015). On the basis of 19 published papers, the authors concluded that online teaching of clinical skills was no less effective than traditional means.…”
Section: Discussionmentioning
confidence: 67%
“…Motivação de alunos de enfermagem no uso das tecnologias da informação e comunicação Assim como no contexto internacional (4,13) , no (1)(2)(3)5,10,12) , também é válida a reflexão sobre a tangibilidade do cuidado e a necessidade da interação do estudante com outros profissionais e com o próprio paciente (4) , sobretudo na es- (5) . Não cabe, no espaço deste estudo, discutir a viabilidade de cursos integralmente baseados na EaD, prática não endossada pelo Ministério da Saúde e repudiada pelo Conselho de Classe (5) .…”
Section: Discussionunclassified
“…As propostas de EaD que aplicaram as TICs de forma inovadora e criativa apresentaram resultados positivos para o processo de ensino-aprendizagem (1)(2)(3) . No ensino de conteúdos clínicos, não há evidência de que o ensino a distância comprometa a aprendizagem ou tenha resultados diferentes da modalidade presencial (4) . No entanto, discute-se que o uso demasiado do modelo EaD nos cursos de Enfermagem, para além do limite de 20% da carga horária total do curso autorizada pelo Ministério da Educação brasileiro, pode comprometer a formação das competências profissionais, sobretudo nas dimensões técnicas e relacionais.…”
Section: Introductionunclassified
“…"All forms of electronically supported or mediated learning and teaching" [30]. [4,12,42,[46][47][48] Face-to-Face learning "A learning process where learners and experts are present physically in same place at same time" [49]. [25,[49][50][51][52] Game-based learning " [It] refers to the borrowing of certain gaming principles and applying them to real-life settings to engage users" [53].…”
Section: Eai Endorsed Transactionsmentioning
confidence: 99%